2009
DOI: 10.1104/pp.109.145532
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2A.Z Regulates the Expression of Several Classes of Phosphate Starvation Response Genes But Not as a Transcriptional Activator

Abstract: Phosphate (Pi) availability is a major constraint to plant growth. Consequently, plants have evolved complex adaptations to tolerate low Pi conditions. Numerous genes implicated in these adaptations have been identified, but their chromatin-level regulation has not been investigated. The nuclear actin-related protein ARP6 is conserved among all eukaryotes and is an essential component of the SWR1 chromatin remodeling complex, which regulates transcription via deposition of the H2A.Z histone variant into chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 48 publications
6
160
1
Order By: Relevance
“…In rice, SPX1 is partly involved in regulating the induction of some Pi transporters (Wang et al 2009b). Histone H4 (Os04t0583600) and histone H2B (Os05t0574300) were upregulated in shoot during early -P stress whereas histone H1 (Os03t0799000) and histone H2B (Os01t0152900) were downregulated in shoot during late -P stress thereby supporting the chromatin-level regulation of response to Pi starvation (Smith et al 2010). Under ++P stress treatments, OsIPS1 and OsIPS2 did not show any specific pattern of expression in either root or shoot.…”
Section: Characterization Of Pi Stress-responsive Transcriptsmentioning
confidence: 99%
“…In rice, SPX1 is partly involved in regulating the induction of some Pi transporters (Wang et al 2009b). Histone H4 (Os04t0583600) and histone H2B (Os05t0574300) were upregulated in shoot during early -P stress whereas histone H1 (Os03t0799000) and histone H2B (Os01t0152900) were downregulated in shoot during late -P stress thereby supporting the chromatin-level regulation of response to Pi starvation (Smith et al 2010). Under ++P stress treatments, OsIPS1 and OsIPS2 did not show any specific pattern of expression in either root or shoot.…”
Section: Characterization Of Pi Stress-responsive Transcriptsmentioning
confidence: 99%
“…In Arabidopsis, it has also been implicated in both positive and negative transcriptional regulation. Mutations in the components of SWR1-C cause the derepression of biotic and abiotic plant response genes, such as plant disease resistance genes, heat shock-induced genes, and phosphate starvation response genes, supporting the negative role of H2A.Z (MarchDíaz et al, 2008;Kumar and Wigge, 2010;Smith et al, 2010). By contrast, the mutations cause the suppression of the developmentally regulated FLC gene, supporting the positive role of H2A.…”
Section: Recruitment Of Chromatin Modification Factors and General Trmentioning
confidence: 99%
“…For example, it has been reported that modifications in chromatin structure through the deposition of the histone variant H2A.Z are involved in the activation of numerous genes associated with Pi deficiency. These findings suggest that chromatin remodeling could play an important role in modulating the transcriptional activation or repression of PSR genes (26). However, to what extent and which epigenetic marks modulate the Pi starvation response remains largely unknown.…”
mentioning
confidence: 96%